A comparison of oscillating sweeping jet and steady normal jet in cooling gas turbine leading edge: Numerical analysis. (July 2023) - Khan, Mohammed S.; Hamdan, Mohammad O.; Al-Omari, Salah A.B.; Elnajjar, Emad
Highlights: Unsteady k-ω CFD simulations were performed to compare the fluid dynamics and heat transfer performance of sweeping jets generated by seven fluidic oscillator jets arranged on a longitudinal array across a target surface to those of seven steady jets. Compared with the steady jet case, the average heat transfer performance of the sweeping jet case exhibited better temperature and Nusselt number uniformity in the zone directly affected by the jet and the zone downstream. The results clearly show that the steady jet case has significantly higher temperature and hotspot temperature points on the target surface. The sweeping jets of the fluidic oscillator array produced higher average Nu values and a more uniform temperature distribution on the target surface than in the steady jet case. The time-averaged Nu number predicted by the sweeping jet was 12.2% higher than that predicted by the steady jet. The sweeping jets had better heat removal performance. Abstract: Impinging jets have emerged as a prominent cooling technology in the gas turbine industry. With the addition of fluidic oscillators as heat removal devices, steady-state impinging jets can be converted to sweeping impinging jets, presenting an opportunity to improve the heat transfer performance of current impinging jets by covering a larger cooling surface area on the leading edge of a gas turbine blade. Sweeping jets are self-oscillating devices that operate based on the Coanda effect, making them self-sustaining. In this study, the flow and heat transfer performance of an array of seven steady and sweeping impinging jets were investigated using the unsteady Reynolds-averaged Navier-Stokes turbulent SST k-ω model. The sweeping jet impingement improved the heat removal performance by cooling a larger surface area of the leading edge with a constant heat flux and by improving the overall time-averaged cooling effectiveness. Compared with the steady jet case, the sweeping jet case shows an improvement in heat transfer of 12.2%. Further, the use of fluidic oscillators (sweeping jets) produced a more uniform mass flow rate distribution from all jets compared with a simple jet.